Bullying Among Junior High School Adolescents in Sorong City: A Pilot Survey - Butet Agustarika; Rizqi Alvian Fabanyo; Yogik Setia Anggreini; Deborah Ferdinanda Lumenta (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Adolescent bullying has become a widespread public health issue and a global concern. This behavior significantly impacts adolescents' psychological, social, and educational well-being. In Indonesia, numerous bullying cases occur, yet many go unreported, including in Sorong City, West Papua Province. This research aims to identify bullying cases experienced by adolescents in junior high schools in the Sorong City area This is a descriptive research. The study population was junior high school adolescents in Sorong City, with a sample of 165 selected through cluster random sampling based on inclusion criteria. Data were collected using the Multidimensional Peer-Victimization Scale-24 (MPVS-24) Bullying Incident Questionnaire and analyzed with descriptive tests in SPSS version 25. The research findings were gathered from 165 junior high school students in Sorong City. The students were categorized as follows: normal (44.8%), bullying victims (36.4%), bullying perpetrators (10.3%), and bystanders (8.5%). These results indicate the prevalence of bullying behavior in junior high schools in Sorong City. It is important to implement follow-up strategies to prevent adverse effects on the victims, perpetrators, and bystanders. Collaboration among parents, schools, health professionals, and the government is essential to address and prevent bullying among adolescents in the school environment.